Economic Cycle and Innovative Activity of Enterprises in Polish Regions — Probit Models - Świadek, Arkadiusz; Szopik-Depczyńska, Katarzyna (Regional Barometer. Analyses & Prognoses, 2011)
In the paper the results of the analysis of impact of economic cycle on the innovative activity of enterprises in Polish regions were presented. Firms from dolnośląski, mazowiecki, śląski and zachodniopomorski region in years 2007–2010 were investigated. For evaluation of relations between different indicators of innovative activity and the independent variable which was one of the phase of economic cycle (expansion, slowdown, downturn) one factor probit model was applied.